2012
DOI: 10.7150/ijbs.8.195
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Signaling and Cardiovascular Diseases

Abstract: Transforming growth factor  (TGF) family members are involved in a wide range of diverse functions and play key roles in embryogenesis, development and tissue homeostasis. Perturbation of TGF signaling may lead to vascular and other diseases. In vitro studies have provided evidence that TGF family members have a wide range of diverse effects on vascular cells, which are highly dependent on cellular context. Consistent with these observations genetic studies in mice and humans showed that TGF family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 145 publications
1
79
0
3
Order By: Relevance
“…Accordingly, chronic infusion of BMP4 in mice leads to endothelial dysfunction and arterial hypertension [69]. It has been shown that BMP4 is increased in response to a high fat diet which then leads to upregulated BMP2 and -4 expression and an proinflammatory effect on the endothelium surface [70,71]. Initially ECs in lesion-prone areas experience unstable flow conditions, such as low shear stress and oscillatory shear stress (OS), which induces BMP4 expression and stimulates the production of ROS in a nox1-and p47phox-dependent manner.…”
Section: Bmps In Inflammatory Vascular Diseasesmentioning
confidence: 99%
“…Accordingly, chronic infusion of BMP4 in mice leads to endothelial dysfunction and arterial hypertension [69]. It has been shown that BMP4 is increased in response to a high fat diet which then leads to upregulated BMP2 and -4 expression and an proinflammatory effect on the endothelium surface [70,71]. Initially ECs in lesion-prone areas experience unstable flow conditions, such as low shear stress and oscillatory shear stress (OS), which induces BMP4 expression and stimulates the production of ROS in a nox1-and p47phox-dependent manner.…”
Section: Bmps In Inflammatory Vascular Diseasesmentioning
confidence: 99%
“…These genes included cartilage oligomeric matrix protein (Comp) and matrix Gla protein (Mgp), which encode glycoproteins that bind BMP-2 and BMP-4. 51,53,54 Interestingly, up-regulation and localization of COMP and MGP in cardiovascular calcification lesions have been reported. 52,55e58 Thus, the heat-induced testicular calcification observed here might be similar to calcification in the cardiovascular system.…”
Section: Heat-induced Testicular Calcificationmentioning
confidence: 95%
“…31 Notably, endogenous BMP antagonists, such as noggin and chordin, may inhibit vascular calcification. 51,60 Interestingly, transgenic mice overexpressing GREM1, a BMP antagonist with 42.9% amino acid sequence similarity to GREM2, exhibit severe osteopenia, ectopic calcification, and thinning of the dentin and enamel in the teeth. 61 Thus, GREM2 could act similarly as an inhibitor of calcification by antagonizing BMP activity.…”
Section: Heat-induced Testicular Calcificationmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased expression of TβRI and TβRII in sclerodermal fibroblasts suggests that increased production of type I collagen by autocrine TGF-β signalling leads to aberrant ECM deposition and scarring. Therapeutic approaches to scleroderma have included inhibition of TGF-β activity in sclerotic tissue with GC-1008 and Disitertide (P144) showing efficacy in clinical trials phase I and II respectively [76] [77] after CAT-192 failure to show evidence of efficacy in a study on the treatment of patients with early-stage systemic scleroderma [22].…”
Section: • Fibrosismentioning
confidence: 99%